The Effects of Eustatic Sea Level Change in the Development of Carbonate Reservoir: An Overview - Herman Darman (Berita Sedimentologi, 1998)
There are some major factors that control the variations in stratal patterns and lithofacies distributions within carbonate rocks. They include tectonic subsidence, eustatic change of sea-level, sediment volume, and climate. However, the major control over carbonate sedimentations is the eustatic change of sea-level.The cyclic changes in global sea level produce reciprocal sedimentations that alternately open and shut off transport of terrigenous clastics across the shelf into the basain. These clastics are highly involved in carbonate deposits development. During high stand of sea level, carbonates are the dominant lithologies that accumulates on the shelf, shelf margin, and in the basin. During succedingly lower stands of sea level, terrigenous clastics progrades across the shelf, and initial clastic sedimentation occures as they by-passes the slope and accumulates in the basin.Sea-level changes not only controls the carbonate sedimentation, but also controls the thickness and the internal structures of the carbonate rocks. Various depositional environments produce by the sea level changes cause the heterogeneity of carbonate reservoir. The sea level changes are highly related to the carbonate reservoir creation, therefore it is important to understand their relationship.